Association Between Insulin Resistance and Remote Diffusion-Weighted Imaging Lesions in Primary Intracerebral Hemorrhage - Ye, Xiang-hua; Zhang, Jian-li; Jin, Yu-jia; Shen, Dan; Hao, Xiao-di; Li, Jia-wen; Zhong, Jia-wei; Jin, Lu-hang; Tong, Lu-sha; Gao, Feng (Frontiers in Immunology, 2021)
Background Abnormal glucose metabolism was shown to be associated with the occurrence of remote diffusion-weighted imaging lesions (R-DWILs) after primary intracerebral hemorrhage (ICH) onset. Insulin resistance is a metabolic disorder that regarded as an indicator of chronic systemic inflammation. In this study, we aimed to determine the effect of insulin resistance on the occurrence of R-DWILs in ICH. Methods Patients with primary ICH within 14 days after onset were prospectively enrolled from November 2017 to October 2019. R-DWILs was defined as remote focal hyperintensity from the hematoma in DWI, with corresponding hypointensity in apparent diffusion coefficient. The homeostasis model assessment of insulin resistance (HOMA-IR) was used for insulin resistance estimation and calculated as fasting insulin (μU/mL) × fasting glucose (mmol/L) / 22.5. Patients in our cohort were divided into four groups according to HOMA-IR index quartiles. Logistic regression analysis were used to evaluate the association of HOMA-IR with R-DWILs occurrence. Sensitivity analysis was performed in non-diabetic patients, non-obese patients, hypertensive ICH patients and patients with age ≥60y separately. The association between HOMA-IR and systemic inflammatory immune indices neutrophil to lymphocyte ratio (NLR) and monocyte to lymphocyte ratio (MLR) was examined with multiple linear regression analysis. Results Among 345 patients, 54 (15.7%) had R-DWILs. Both the third and fourth quartiles of HOMA-IR index were robustly associated with an increased risk of R-DWILs occurrence (adjusted OR 3.58, 95% CI 1.33-9.65; adjusted OR 3.91, 95%CI 1.47-10.41) when compared with the first quartile. The association was consistent in non-diabetic, non-obese, hypertensive ICH patients as well as in patients ≥60 years old. Furthermore, both NLR and MLR were independently associated with HOMA-IR. Conclusions Our study suggested that insulin resistance evaluated with HOMA-IR index was independently associated with the presence of R-DWILs in patients with acute and subacute primary ICH. It may provide new insights into the metabolism-related brain injury after ICH ictus.